Herbivoria de Bosmina freyi e suas relações ecológicas no Reservatório de Itupararanga - Votorantim/SP - Magalhães, Raphaella de Abreu (2014)
Preliminary studies on reservoir Itupararanga indicate that the seasonal dynamics of plankton community is not being strongly controlled by bottom-up forces. Cianobactéria Cylindrospermopsis raciborskii and clorofícea Monoraphidium contortum are the dominant phytoplankton species in this reservoir. Bosmina freyi, recently described, is the dominant zooplankton in Itupararanga and there is no records of studies feeding habits of this specie. Therefore, the present study aims to assess the importance of the cladoceran Bosmina freyi as consumers of phytoplankton species: Monoraphidium contortum and Cylindrospermopsis raciborkii to better understand the ecological role of this organism in the planktonic food web in reservoir Itupararanga. M. contortum and three types of strain C.raciborskii, toxic strain (Cy.tox), strain with large filaments (Cy.grd) and strain with small filaments (Cy.peq) where ofered for Bosmina freyi. For each treatment, were calculated the density, cell volume, biovolume before and after incubation with B. freyi.Also calculated the ingestion and filtration rates. Qualitative models have also been made to describe and make predictions on the plankton community Itupararanga when there are changes in the population of Chaoborus sp. It was noted that B. freyi is able to efficiently ingest C.raciborskii including toxic strain, but presented difficulties in filter and ingest filaments of Cy.grd.Besides, B.freyi seems to be able to cut up filaments of C.raciborskii for ingestion. No food preference was observed by M.contortum. Qualitative models made in this study corroborate the hypothesis that seasonal variations in plankton reservoir Itupararanga may be being controlled by top-down forces due the presence of Chaoborus sp.